Mathematical model of track cycling: the individual pursuit - Underwood, L.; Jermy, M. (Procedia Engineering, 2010)
Mathematical modelling has been used to predict the performance of cyclists for a number of years. The aim of this study was to develop a mathematical model for Individual Pursuit (IP) cyclists on an indoor velodrome, taking into account the effects of leaning in the bends and the actual position of the rider on the track using data collected by the SRM training system. This model uses forward integration to predict the velocity of the centre of mass and the finishing time for IP athletes, accurate to within 3% with currently available input data.